2017
DOI: 10.3389/fcimb.2017.00369
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Droplet PCR to Detect Mycobacterium tuberculosis DNA in Whole Blood-Derived DNA Samples from Patients with Pulmonary and Extrapulmonary Tuberculosis

Abstract: Tuberculosis (TB) is a chronic infectious disease that has been threatening public health for many centuries. The clinical diagnostic procedure for TB is time-consuming and laborious. In the last 20 years, real-time fluorescence-based quantitative PCR (real-time PCR) has become a better alternative for TB diagnosis in clinics due to its sensitivity and specificity. Recently, digital droplet PCR (ddPCR) has been developed, and it might be an ideal alternative to conventional real-time PCR for microorganism dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 22 publications
(26 reference statements)
1
48
0
Order By: Relevance
“…Once PCR amplification has been carried out within each of these 20 000 droplets, fluorescent positive and negative droplets are measured and the concentration of target DNA is determined by a Poisson algorithm. Although ddPCR has shown to be a technique with potential and has been used for the detection of specific pathogens, its use in the setting of rapid BSI detection has not been explored yet (Yang et al , ; Li et al, ; Song et al , ; Wang et al , ). The use of broad‐range primers for the amplification of the highly conserved bacterial 16S rRNA and fungal 28S rRNA, and different fluorescence dye‐labelled probes, enables the detection of BSIs, discrimination between fungal and bacterial infections, and –in the latter case – specification of their Gram stain differentiation or genus (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Once PCR amplification has been carried out within each of these 20 000 droplets, fluorescent positive and negative droplets are measured and the concentration of target DNA is determined by a Poisson algorithm. Although ddPCR has shown to be a technique with potential and has been used for the detection of specific pathogens, its use in the setting of rapid BSI detection has not been explored yet (Yang et al , ; Li et al, ; Song et al , ; Wang et al , ). The use of broad‐range primers for the amplification of the highly conserved bacterial 16S rRNA and fungal 28S rRNA, and different fluorescence dye‐labelled probes, enables the detection of BSIs, discrimination between fungal and bacterial infections, and –in the latter case – specification of their Gram stain differentiation or genus (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The study described Digital PCR was more sensitive than real-time PCR or Sanger sequencing and could detect mutant DNA even at a 1000:1 mixture of H37Rv:XDR TB [27] . The first work demonstrating the diagnosis of TB in clinics used the peripheral blood of patients with pulmonary TB and extrapulmonary TB and indicates that ddPCR has advantages over real-time PCR for detecting low numbers of copies of MTB DNA [12] . In our previous study, we have found the EGFR T790M detection using of ddPCR is proved to be more sensitive than ARMS-PCR [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Droplet digital PCR is a newly developed technology that has many advances upon real-time PCR. Recently, researchers reported ddPCR could be used for the detection of TB in whole blood-derived DNA samples and stable Mtb strain [12,13] . However, the use of ddPCR for the detection of TB pathogen in FFPE samples is not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted that it allows for the identification and quantification of DNA from tissue samples and peripheral blood where it is difficult to detect . This method has been used for the rapid diagnosis of the extra‐pulmonary infection of tuberculosis, showing a much better detection capacity than quantitative polymerase chain reaction (qPCR), which only manages to detect the microorganism in half the patients diagnosed by ddPCR from different body samples, including the bone …”
Section: Discussionmentioning
confidence: 99%